2022
DOI: 10.1186/s12935-022-02809-2
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 promotes glycolysis and cholangiocarcinoma progression by mediating the m6A modification of AKR1B10

Abstract: Objective N6-methyladenosine (m6A) RNA methylation is involved in governing the mechanism of tumor progression. We aimed to excavate the biological role and mechanism of the m6A methyltransferase METTL3 in cholangiocarcinoma (CCA). Methods METTL3 expression was determined by database and tissue microarray analyses. The role of METTL3 in CCA was explored by loss- and gain-of-function experiments. The m6A target of METTL3 was detected by RNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…METTL3, an important RNA methyltransferase, plays a critical role in RNA modification, and its expression and catalysed RNA m6A modification are associated with the occurrence and progression of various human diseases 10–12,14 . Prior studies have demonstrated that METTL3 is overexpressed in various cancers and contributes to cancer progression and metastasis 21,46–55 . In this study, we further confirmed through multi‐data set analysis that the expression of METTL3 was significantly higher in tumour samples than in the control group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…METTL3, an important RNA methyltransferase, plays a critical role in RNA modification, and its expression and catalysed RNA m6A modification are associated with the occurrence and progression of various human diseases 10–12,14 . Prior studies have demonstrated that METTL3 is overexpressed in various cancers and contributes to cancer progression and metastasis 21,46–55 . In this study, we further confirmed through multi‐data set analysis that the expression of METTL3 was significantly higher in tumour samples than in the control group.…”
Section: Discussionsupporting
confidence: 76%
“…[10][11][12]14 Prior studies have demonstrated that METTL3 is overexpressed in various cancers and contributes to cancer progression and metastasis. 21,[46][47][48][49][50][51][52][53][54][55] In this study, we further confirmed through multi-data set analysis that the expression of METTL3 was significantly higher in tumour samples than in the control group. ROC results indicated that its expression the expression of ER target genes and limits the growth of breast cancer cells.…”
Section: Discussionsupporting
confidence: 75%
“…previous studies demonstrated that glycolysis, as metabolic reprogramming, contributed significantly to cholangiocarcinoma initiation and progression [ 43 , 44 ] Glycolic pathways and enzymes, including pyruvate kinase M2 [ 45 , 46 ], Aldolase A [ 47 ] and lactate dehydrogenase A [ 48 ], play a critical role in BTC and have been utilized as biomarkers to predict patients` outcomes. Targeting glycolysis could be considered as a promising treatment option in BTC [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mechanism, YTHDF2 accelerated degradation of m6A-modified LATS1 mRNA, thus reduced phosphorylation of YAP/TAZ and activated it. 223 In addition to these compelling transcription factors (TFs), METTL3 boosted expression of NDUFA4 in GC, 224 AKR1B10 in cholangiocarcinoma (CCA), 225 NCAPH in clear cell renal cell carcinomas (ccRCC), 226 thus promoted glycolysis and malignant phenotypes. Notably, METTL3-induced m6A interacted with ncRNAs to improve glycolysis, such as stabilizing effects on lncRNA ABHD11-AS1 in NSCLC, 227 lncRNA SNHG7 in prostate cancer (PC), 228 circQSOX1 in CRC, 229 and linc-UROD in PC, 230 which are generally mediated by IGF2BPs.…”
Section: Rna Modifications and Cellular Metabolismmentioning
confidence: 99%